Comparative reproductive biology (Blackwell Pub, 2007)
Written by renowned scientists in their respective fields, Comparative Reproductive Biology is a comprehensive reference on the reproductive systems of domestic species. The book offers both broad and specific knowledge in areas that have advanced the field in recent years, including advances in cell and molecular biology applied to reproduction, transgenic animal production, gender selection, artificial insemination, embryo transfer, cryobiology, animal cloning and many others. This seminal text includes topics in animal reproduction that are usually only found as part of other books in animal science such as anatomy, histology, physiology, radiology, ultrasonogrophy, and others.